Microplastics in Aquatic Environments: A Systematic Review of Distribution and Biological Effects in Waters, Sediments, and Biota - Ayuni, Ni Putu Sri; Watiniasih, Ni Luh; Suyasa, I Wayan Budiarsa; Hendrawan, I Gede (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Currently, the issue of microplastic pollution in aquatic ecosystems is a significant cause for worry. Microplastics, which are tiny pieces of plastic, are readily absorbed by freshwater organisms, leading to detrimental impacts on their growth, reproduction, predatory abilities, and other aspects. This study aims to review the scientific literature on microplastics in freshwater environments including waters, sediments, and biota in order to identify their existence and impact. For such, a systematic review was conducted, following the PRISMA guidelines, applying a descriptive and statistical analysis to the data. The original research articles in "microplastics in freshwaters". Up to 177 papers involving microplastic in freshwaters, published between 2013 and 2023, are identified in the Publish or Perish. Of the 177 articles, 66 are excluded because they include review articles. Finally, this review will to assess the excistence and influence microplastics in water, sediment and biota, in freshwater environmental.